A call to incorporate a reproductive justice agenda into reproductive health clinical practice and policy - Gilliam, Melissa L.; Neustadt, Amy; Gordon, Rivka (Contraception, 2009)
Keywords: approches et analyses; contraception; discipline; droits des femmes*; intersectionnalité; inégalités; justice reproductive; justice sociale; médecine; ressource en ligne; santé; santé des femmes*; sciences; sciences humaines; sexologie; systèmes d'oppressions; thématiques

From gender bias to gender awareness in medical education - Verdonk, Petra; Benschop, Yvonne W. M.; de Haes, Hanneke C. J. M.; Lagro-Janssen, Toine L. M. (Advances in Health Sciences Education, 2009)
Gender is an essential determinant of health and illness. Gender awareness in doctors contributes to equity and equality in health and aims towards better health for men and women. Nevertheless, gender has largely been ignored in medicine. First, it is stated that medicine was ‘gender blind’ by not considering gender whenever relevant. Secondly, medicine is said to be ‘male biased’ because the largest body of knowledge on health and illness is about men and their health. Thirdly, gender role ideology negatively influences treatment and health outcomes. Finally, gender inequality has been overlooked as a determinant of health and illness. The uptake of gender issues in medical education brings about specific challenges for several reasons. For instance, the political-ideological connotations of gender issues create resistance especially in traditionalists in medical schools. Secondly, it is necessary to clarify which gender issues must be integrated in which domains. Also, some are interdisciplinary issues and as such more difficult to integrate. Finally, schools need assistance with implementation. The integration of psychosocial issues along with biomedical ones in clinical cases, the dissemination of literature and education material, staff education, and efforts towards structural embedding of gender in curricula are determining factors for successful implementation. Gender equity is not a spontaneous process. Medical education provides specific opportunities that may contribute to transformation for medical schools educate future doctors for future patients in future settings. Consequently, future benefits legitimize the integration of gender as a qualitative investment in medical education.
Keywords: approches et analyses; discipline; europe; formation des médecins; médecine; pays-bas; projet charge mentale; rapports sociaux de sexe; régions géographiques; santé; sciences; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; éducation

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Number: 1
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

L’impact des violences structurelle et conjugale en contexte migratoire: Perceptions d’intervenants pour le contrer - Rojas-Viger, Celia (Nouvelles pratiques sociales, 2008)
Résumé Le Canada et le Québec, sociétés pluriethniques, possèdent des politiques et des programmes de promotion et de prévention pour contrer les violences faites aux femmes, mais reconnaissent que le défi est de taille dans le contexte migratoire. Les immigrantes, confrontées à la violence conjugale, ne disposent souvent pas d’accessibilité culturelle aux services sociaux et de santé ou n’obtiennent pas de réponse adéquate à leurs besoins. Toutefois, certains organismes ont des projets pour leur venir en aide mais ils ne sont pas systématiques. L’article présente les résultats d’une recherche exploratoire, avec approche ethnologique, qui documente la perception de 10 intervenants d’organismes communautaires et institutionnels concernant leurs activités dans le domaine et leur préoccupation pour la promotion et la prévention primaire, même si leurs pratiques concrètes sont surtout centrées sur la prévention secondaire. Maints empêchements les limitent, mais leurs perceptions des réponses promotionnelles et préventives mettent en lumière l’impact de la violence structurelle et de la violence conjugale et orientent les perspectives de renouvellement des pratiques d’intervention sociosanitaire en matière de violence conjugale.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; canada; care; cours; discipline; histoire et politique; intersectionnalité; inégalités; justice sociale; migration; médecine; premier cycle; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences; sciences humaines; sex2283; systèmes d'oppressions; thématiques; trs3500; violence systémique; violences; violences conjugales

Contested pleasures: The sociopolitical economy of disability and sexuality - Shildrick, Margrit (Sexuality Research & Social Policy, 2007)
Consideration of sexual pleasure in the lives of people with disabilities plays little part in lay consciousness, and practically none in social policy. This article investigates such repression by engaging with a cultural imaginary that fears nonnormative sexuality as being a potential point of societal breakdown. Recent work in disability studies gives a very different understanding of the sexuate body that opens up the parameters of sexuality for everyone. This work challenges current social policy’s supposedly rational utilitarian basis and the principle of equality that together ground a sociopolitical economy of disability predicated on rehabilitation or compensation. Nonetheless, the call for sexual citizenship for people with disabi lities is fraught with difficulties, not least regarding the potential extension of govern mentality. An effective approach not only will take into account the sociopolitical aspects of this issue but also will respond to both the full embodiment of disability and its significance in mainstream culture.
Keywords: EDI; accessibilité; approches et analyses; arts; bioéthique; capacitisme; corps; cours; discipline; intersectionnalité; justice sociale; philosophie; premier cycle; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires

The Cyborg Embryo: Our Path to Transbiology - Franklin, S. (THEORY CULTURE AND SOCIETY, 2006)
It is useful on the occasion of the 21st anniversary of the ‘Cyborg Manifesto’ not only to reconsider its lessons in the context of what is frequently described as the re-engineering of ‘life itself’, but to look at Haraway’s earlier work on embryos. In this article I begin with Haraway’s analysis of embryology in the 1970s to suggest her cyborg embryo was already there, and has, if anything, gained relevance in today’s embryo-strewn society. I argue further, as the title suggests, that the cyborg embryo has been crucial in defining our path to what I am calling here, building on Haraway’s notion of trans from Modest_Witness, ‘transbiology’ - broadly meaning stem cell research, cloning, tissue engineering and regenerative medicine. To illustrate this argument I draw on recent ethnographic fieldwork in a new stem cell derivation facility in the UK built adjacent to an IVF surgery. Using this example, I explore the important and paradoxical role of IVF in the emergence of stem cell science, cloning and transbiology, suggesting that Haraway’s analysis remains crucial to understanding the ironic and contradictory, and unexpectedly generative, circumstances through which the IVF-stem cell interface - the door to transbiology - came into being.
Keywords: approches et analyses; biologie; care; corps; cours; discipline; discours dominant; fecondation in vitro; féminisme cyborg; justice reproductive; lit4700; maternité; premier cycle; ressource en ligne; santé; sciences; sciences humaines; sociologie; systèmes d'oppressions; thématiques

The scientific revolution and the death of nature - Merchant, Carolyn (Isis, 2006)
The Death of Nature: Women, Ecology, and the Scientific Revolution, published in 1980, presented a view of the Scientific Revolution that challenged the hegemony of mechanistic science as a marker of progress. It argued that seventeenth-century science could be implicated in the ecological crisis, the domination of nature, and the devaluation of women in the production of scientific knowledge. This essay offers a twenty-five-year retrospective of the book’s contributions to ecofeminism, environmental history, and reassessments of the Scientific Revolution. It also responds to challenges to the argument that Francis Bacon’s rhetoric legitimated the control of nature. Although Bacon did not use terms such as “the torture of nature,” his followers, with some justification, interpreted his rhetoric in that light.
https://nature.berkeley.edu/departments/espm/env-hist/articles/84.pdf
Keywords: approches et analyses; capitalisme; discipline; environnement; projet charge mentale; santé; santé de la nature; sciences; sciences de l'environnement; sexisme; systèmes d'oppressions; thématiques; torture de la nature; violences; écoféminisme

Cerveau, sexe et pouvoir - Vidal, Catherine; Benoit-Browaeys, Dorothée. (Belin, 2005)
À la lumière des connaissances actuelles en neurosciences, on serait tenté de croire que les vieux préjugés sur les différences biologiques entre les hommes et les femmes ont été balayés. Ce n'est manifestement pas le cas : médias et ouvrages de vulgarisation prétendent que les femmes sont " naturellement " bavardes et incapables de lire une carte routière, tandis que les hommes sont nés bons en maths et compétitifs. Ces discours laissent croire que nos aptitudes, nos émotions, nos valeurs sont tablées dans des structures mentales immuables depuis les temps préhistoriques. Cet ouvrage, qui s'adresse à un large public, replace le débat autour de la différence des sexes sur un terrain scientifique rigoureux, au-delà des idées reçues. L'enjeu est de comprendre le rôle de la biologie, mais aussi l'influence de l'environnement social et culturel dans la construction de nos identités d'hommes et de femmes. Notre destin n'est pas inscrit dans notre cerveau! [Source : d'après la 4e de couv.].
Keywords: 2000 à aujourd'hui; approches et analyses; corps; cours; discipline; discours dominant; inégalités; neuropsychologie; neurosciences; premier cycle; psy4910; psychologie; périodes historiques; sciences; sciences humaines; sexe/genre; sexisme; systèmes d'oppressions; thématiques

La grande arnaque : sexualité des femmes et échange économico-sexuel - Tabet, Paola (L'Harmattan, 2004)
Dans la majorité des sociétés connues, la sexualité apparaît comme un échange asymétrique et non réciproque entre hommes et femmes, une compensation masculine pour une prestation féminine, un paiement qui peut revêtir les formes les plus variées en échange d'une sexualité transformée en service. Comment se fait-il que les hommes, même plongés dans les situations les plus misérables, peuvent se payer le service sexuel d'une femme - alors que non seulement les femmes n'ont pas, sauf exception, cette possibilité mais de plus n' ont même pas droit à leur propre sexualité ?
Keywords: EDI; approches et analyses; cours; cycles supérieurs; discipline; division sexuelle du travail; ethnologie; fem1000; fem7000; inégalités; lit3220; premier cycle; rapports sociaux de sexe; sciences; sciences humaines; sexualité; systèmes d'oppressions; thématiques; épistémologie

Cerveau, sexe et idéologie - Vidal, Catherine (Diogène, 2004)
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; corps; cours; discipline; discours dominant; europe; fem1000; france; neurobiologie; premier cycle; psy4910; périodes historiques; ressource en ligne; régions géographiques; sciences; stéréotypes; systèmes d'oppressions; thématiques

L'invention du naturel : les sciences et la fabrication du féminin et du masculin - Gardey, Delphine; Löwy, Ilana.. (Ed. des Archives contemporaines, 2000)
Comprendre ce que sont les hommes et les femmes, penser la différence entre les sexes a constitué et constitue encore un objet d'investigation et un enjeu politique et social de premier ordre. Des sciences d'hier à celles d'aujourd'hui, des discours et des pratiques médicales aux plus récentes sciences humaines, les auteurs de cet ouvrage révèlent la fragilité des évidences dites sur la nature ou le corps des femmes et des hommes, et insistent sur la force des arrangements et organisations du social qui ont pu en découler. Plus qu'une enquête descriptive sur les états variables des représentations proposées par les sciences, il s'agit d'analyser comment les scientifiques " en société " élaborent les critères de différenciation entre les sexes, contribuant à faire endosser à la nature certaines formes de domination. Convié à découvrir, en France et à l'étranger, l'histoire récente de ces nouveaux terrains d'enquête, le lecteur est aussi invité à méditer sur les effets de longue durée d'une modernité occidentale instaurée sous le signe de l'altérité entre raison et nature, hommes et femmes.
Textes issus de deux journées d'études qui se sont déroulées à la Cité des sciences et de l'industrie à Paris, les 24 janvier et 22 avril 1997.
Keywords: approches et analyses; cours; discipline; discours dominant; essentialisation; genre; histoire et politique; identité sexuelle; naturalisation; premier cycle; production des savoirs; rapports sociaux de sexe; sciences; sciences humaines; sciences sociales; sex3383; sexe/genre; sociologie; systèmes d'oppressions; thématiques; épistémologies féministes